Current approaches to assessment of the impact of the environmental contamination on cancer risk - L. G. Solenova (Успехи молекулярной онкологии, 2020)
The current estimates of the contribution of the environmental contamination to cancer mortality range from 1 to 20 %, being a function of the ecological conditions, the density of industrial enterprises, occupational composition of the population, and others. Assessment of the impact of environmental contamination on cancer risk includes: •setting research priorities on the local, regional, and on the all-Russian levels; •the selection of the research that may be maximally socially profitable; •the choice of the research method that the most adequately meets the research objectives; •systemic analysis of the planed research to determine the availability of the resources, personnel, and information; •monitoring of atmospheric pollutions with analysis of the fraction composition of the particulate matters; •coordination of available data basis on environment and the population health conditions; •the implementation of the of molecular biology to determine prenosological manifestation of carcinogenesis and development of fine and diverse research methods on relationships between the environment and cancer risk.For effective implementation of the research objectives aimed to decrease the impact of hazard factors with special reference on cancer risk in the Russian population, it is necessary: to create training personnel capable of providing epidemiologic studies, using up-to day methods, publication of methodological materials, text books, and sufficient funding of studies.